Updated Segmentation Model of the Aceh Segment of the Great Sumatran Fault System in Northern Sumatra, Indonesia - Aulia Kurnia Hady; Gayatri Indah Marliyani (Journal of Applied Geology, 2021)
We study the Aceh Fault segment, the northernmost segment of the Great Sumatran Fault in western Indonesia. The Aceh Fault segment spans 250 km long, passing through three districts: West Aceh, Pidie Jaya, and Aceh Besar, a region of ~546,143 population. The current segmentation model assumes that the Aceh Fault segment acts as a single fault segment, which would generate closer to an M8 earthquake. This estimation is inconsistent with the ~M6–7 historical earthquake data. We conduct a detailed active fault mapping using an ~8 m resolution digital elevation model (DEM) of DEMNAS and sub-m DEM data from UAV-based photogrammetry to resolve this fault’s segmentation model. Our study indicates that the Aceh Fault is active and that the fault segment can be further divided into seven sub-segments: Beutong, Kuala Tripa, Geumpang, Mane, Jantho, Indrapuri, and Pulo Aceh. The fault kinematics identified in the field is consistent with right-lateral faulting. Our study’s findings provide new information to understand the fault geometry and estimate potential earthquakes’ maximum magnitude along the Aceh Fault segment. These are important for the development of seismic hazard analysis of the area.